Deuteron-deuteron nucleosynthesis considered with accounting of centrifugal and coulomb barriers - Tkachenko, I.V.; Trubnikov, S.V.; Tkachenko, V.I. (Вопросы атомной науки и техники, 2017)
The basic analysis of nuclear reactions in the deuteron-deuteron (dd) system at low energies is carried out. For the case of nuclear dd-fusion special attention is paid to the difference in the height of the Coulomb barriers, which arises from different values of the deuteron radius. It is declared that a centrifugal barrier greatly hinders the nuclear reaction at low energies: in 19 out of 20 allowed transitions there is a strong suppression of nuclear fusion. Only in one single transition (S → S) is there no centrifugal suppression, but in the dd-system this transition is not dominant. Attention is drawn to the prospects (despite the smallness of the cross section) of considering radiation fusion in view of the significant energy release in a single act of reaction.